New technique for introducing the cardiac catheter in ventriculo-atrial shunts - Benedek, Pedro; Estable, Miguel (Cirugía del Uruguay, 1980)
A new technique for introducing the cardü,c. catheter in ventricufoatrial shunts for hydrocephalus through the external jugular vein instead of the classically use! internal jugular vein is described. The advantages of the use of the vena jugularis externa and the authors experience with this technique are presented.